ANALYSIS OF POLITENESS STRATEGIES IN STUDENTS' WHATSAPP CHAT - Ratmo, Ratmo; Cahyani, Ida (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study aims at analyzing types of politeness strategies used by the ten 8th semester students of English Department Faculty of Letters Universitas Pamulang and two PUP students in communicating with their lecturers regarding their study. The politeness strategies analyzed in this study include both positive and negative polite strategies. The data of this study were taken from WhatsApp. Through descriptive qualitative method, the data were collected from the fifth semester English Department students’ WhatsApp messages by screen-shooting the conversations between students and their lecturer. To analyze the data, theory of politeness strategies proposed by Brown and Levinson was applied. The analysis revealed that the students used both negative and positive politeness strategies. Out of 26 data found, 11 of them were identified as positive politeness strategy while the rest (15 of them) most strategies applied were negative politeness strategies. The result of the study provides evidence of the reasons that the students used politeness strategies to maintain and build good relationship with their lecturers as their supervisor to negotiate time for supervision, to share progress of conducting their final projects and to consult problems related to their study.